Amacrine Cells Forming Gap Junctions With Intrinsically Photosensitive Retinal Ganglion Cells: ipRGC Types, Neuromodulator Contents, and Connexin Isoform - Harrison, Krystal R. (Invest Ophthalmol Vis Sci, 2021)
PURPOSE: Intrinsically photosensitive retinal ganglion cells (ipRGCs) signal not only centrally to non-image-forming visual centers of the brain but also intraretinally to amacrine interneurons through gap junction electrical coupling, potentially modulating image-forming retinal processing. We aimed to determine (1) which ipRGC types couple with amacrine cells, (2) the neuromodulator contents of ipRGC-coupled amacrine cells, and (3) whether connexin36 (Cx36) contributes to ipRGC-amacrine coupling. METHODS: Gap junction–permeable Neurobiotin tracer was injected into green fluorescent protein (GFP)–labeled ipRGCs in Opn4(Cre/+); Z/EG mice to stain coupled amacrine cells, and immunohistochemistry was performed to reveal the neuromodulator contents of the Neurobiotin-stained amacrine cells. We also created Opn4(Cre/+); Cx36(flox/)(flox); Z/EG mice to knock out Cx36 in GFP-labeled ipRGCs and looked for changes in the number of ipRGC-coupled amacrine cells. RESULTS: Seventy-three percent of ipRGCs, including all six types (M1–M6), were tracer-coupled with amacrine somas 5.7 to 16.5 µm in diameter but not with ganglion cells. Ninety-two percent of the ipRGC-coupled somas were in the ganglion cell layer and the rest in the inner nuclear layer. Some ipRGC-coupled amacrine cells were found to accumulate serotonin or to contain nitric oxide synthase or neuropeptide Y. Knocking out Cx36 in M2 and M4 dramatically reduced the number of coupled somas. CONCLUSIONS: Heterologous gap junction coupling with amacrine cells is widespread across mouse ipRGC types. ipRGC-coupled amacrine cells probably comprise multiple morphologic types and use multiple neuromodulators, suggesting that gap junctional ipRGC-to-amacrine signaling likely exerts diverse modulatory effects on retinal physiology. ipRGC-amacrine coupling is mediated partly, but not solely, by Cx36.